Media Sosial: Ajang Beribadah melalui Dakwah - Syintia Nurfitria (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2018)
This study aims to understand how social media has become the most favored platform for Islamic preaching (dakwah) in the digital age. Social media not only reflects technological advancement but also serves as an effective means to convey Islamic teachings. The research employs a descriptive qualitative method through field observations and interviews. The findings reveal that preaching is an obligation for every Muslim, and social media is a strategic medium to spread Islamic values, provided that ethical and social norms are respected. Preachers (Da’i) are expected to adapt to technological developments to ensure relevant and impactful communication. This research highlights the importance of wisely utilizing social media for dakwah, always adhering to the Qur'an and Hadith as core guidelines.